MEMBANGUN KESADARAN DAN PERILAKU HIDUP SEHAT MAHASISWI GUNA MENCEGAH KANKER PAYUDARA - Kebayantini, Ni Luh Nyoman; Punia, I Nengah; Zuryani, Nazrina; Nugroho, Wahyu Budi; Kamajaya, Gede; Mahadewi, Ni Made Anggita Sastri (Jurnal Ilmiah Widya Sosiopolitika; Vol 2 No 2 (2020): ISU PARIWISATA DAN KESEHATAN DALAM PERSPEKTIF SOSIAL DAN POLITIK, 2021)
Breast cancer is the second highest prevalence after cervical cancer. In recent years cases of breast tumors that are at risk of becoming cancer are found in women aged 25 years and under. This risk will increase in adolescent girls who have a history of tumors, so there is a 4.37 times more risk of developing breast cancer. Similarly, young women who experience menarche (first menstruation) at the age of <12 years are more likely to develop breast cancer than those who experience menarche aged> 12 years. Busyness undergoing daily routine is also one of the causes of teenagers / young women paying less attention to the health of their breasts. Based on this there have been many campaigns and movements to foster women's awareness of breast cancer such as the BSE movement (Breast Self-Check) and SADANIS (aware of clinical examination). It is unfortunate that this campaign has not been able to touch all circles, especially among students who are very busy with campus life and do not have the awareness to take care of their health. This dedication activity is carried out to increase the awareness of students / young women to maintain breast health. Keywords: breast cancer, health, increase student awareness.